2020
DOI: 10.3390/jof6020062
|View full text |Cite
|
Sign up to set email alerts
|

Basidiospores from Wood-Decay Fungi Transform Laccase Substrates in the Absence of Glucose and Nitrogen Supplements

Abstract: Preparations of bacterial endospores and fungal conidia are applied in biocontrols, biocatalyses, and lignocellulose fermentations. The biocatalytic abilities of basidiospores from mushrooms of the order Agaricales are unknown. To assess their potential in colonizing recalcitrant substrates solely with their inherent resources, spores of the white-rot fungi Stropharia rugoso-annulata (Stru) and Kuehneromyces mutabilis (Kmt, Strophariaceae) were analyzed for surface-bound and internal total carbohydrates, pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Cultivation substrates include both cellulosic straw and lignin sawdust. Most studies have considered it an LD [9,16]; however, some reports have classified it as a WR [17,18]. It has been reported that LD fungi shares with WR fungi the plesiomorphic enzymatic network involved in cellulose decomposition, whereas genomic signatures related to hemicellulose-and lignin-degradation genes can separate LD fungi from most WR fungi [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation substrates include both cellulosic straw and lignin sawdust. Most studies have considered it an LD [9,16]; however, some reports have classified it as a WR [17,18]. It has been reported that LD fungi shares with WR fungi the plesiomorphic enzymatic network involved in cellulose decomposition, whereas genomic signatures related to hemicellulose-and lignin-degradation genes can separate LD fungi from most WR fungi [25].…”
Section: Discussionmentioning
confidence: 99%
“…From an ecophysiological point of view, saprotrophic basidiomycetes can be classified into three partially overlapping groups, namely, brown rot (BR), white rot (WR), and litterdecomposing (LD) fungi. S. rugosoannulata can assimilate both cellulosic straw and lignin sawdust; it is categorized as LD [9,16] or WR [17,18]. This is different from a typical LD, such as Agaricus bispora, which is usually cultivated on wheat and rice straw.…”
Section: Introductionmentioning
confidence: 99%